The Role of Religious Commitment, Religious Self-Identity on Consumer’s Willingness to Pay for A Halal Product - Rahma Elsitasari; Asmai Ishak (Profesional Muda Cendekia Publishing, 2021)
This research aims to analyze consumer's willingness to pay toward halal products through the role of religious commitment, religious self-identity, using the theory of planned behavior. This study examines the willingness to pay consumers based on the consumption experiences of well-known foreign franchise restaurants in Indonesia. The data was collected through 250 Muslim students in Yogyakarta. The survey was filled by Google form. Data were analyzed using structural equation modeling, employing the partial least square method (PLS). Findings of the research show that the attitude and the religious self-identity have no impact on the willingness to pay for the halal product, while the perceived behavioral control, the subjective norm, and the religious commitment have a positive and significant effect on the willingness to pay. Additionally, religious commitment has a positive and significant influence on the attitude, and on the religious self-identity. The practical implication of this study suggests the marketers should understand those variables that influence consumers' willingness to pay for halal-certified products from foreign franchise restaurants, namely the subjective norms, the perceived behavioral control, and the religious commitment.